SISTEM PENUNJANG KEPUTUSAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PEMILIHAN JURUSAN PADA KAMPUS NEGERI - Harvey Guharelvino Prabowo (2023)
Students in high school at this time must find or determine the interests of their respective students to be able to continue further learning to university. Based on the law, students must have an interest in what field they are interested in. That way the purpose of this study is to create a decision support system (SPK) to determine the specialization of student majors in the SMA Angkasa 2 environment using the simple additive weighting (SAW) method and calculations on the rigorous capacity of each specialization department at UPNVJ, UNJ, and UINJ state campuses. The use of the simple additive weighting (SAW) method and the calculation of the tightness of the capacity aims to pay attention to the weight and each criterion to the specialization department and then calculate the capacity of the tightness of the specialization department at each state campus so that the results released by the calculation have provided decision support to students to determine the specialization and state campus more precisely. The results of the study succeeded in providing different recommendations to each state university for students with 99% accuracy between the simple additive weighting (SAW) calculation system and the system application on Android. And the system will use the Kotlin programming language and an android-based NoSQL MongoDB database which will contain features for students to see the results of recommendations from the calculation results with the simple additive weighting (SAW) method.